2016
DOI: 10.1088/1757-899x/161/1/012102
|View full text |Cite
|
Sign up to set email alerts
|

The use KPI's to determine the waste in production process

Abstract: Abstract. In theory and practice of management is well-known Lean approach about forms of waste from production processes (Muda) and the method VSM (Value Stream Map), one of the most effective methods for determining the activities generating value within industrial companies. It is also obvious concern of the specialists for performance measurement regardless of purview of the organizations. The literature review has shown that the link between performance indicators and the objectives of the companies is re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Section E contains the study's dependent variable, namely job performance. Five questions for this section were adapted from Borsos (24) and Ahmad (25).…”
Section: Methodsmentioning
confidence: 99%
“…Section E contains the study's dependent variable, namely job performance. Five questions for this section were adapted from Borsos (24) and Ahmad (25).…”
Section: Methodsmentioning
confidence: 99%
“…Below are the checklist questions: Performance indicators : The performance measurement is essential in the management process. Numerous studies have shown that, to adopt the best decisions for the development of the organization, managers must have accurate and current data on the performance of processes taking place within the company (Borsos et al , 2016) (Table II). Continuous improvement (CI) : CI is one of the core strategies for manufacturing excellence and it is considered vital in today’s business environment.…”
Section: Methodsmentioning
confidence: 99%
“…Garretson et al [37], concentrated on the terminology that supports manufacturing process characterization and assessment. Borsos et al [38], explored the relationship between the KPIs and the objectives set by the manufacturing industries in order to determine the waste in the production process. Muhammed et al [39], cited few manufacturing KPIs and implemented them on multi robot line simulator to improve its performance from the results obtained by the KPIs.…”
Section: Literature Reviewmentioning
confidence: 99%